Comparing HIV‐1 and HIV‐2 infection: Lessons for viral immunopathogenesis. (26th February 2013) - Nyamweya, Samuel; Hegedus, Andrea; Jaye, Assan; Rowland‐Jones, Sarah; Flanagan, Katie L.; Macallan, Derek C.
SUMMARY: HIV‐1 and HIV‐2 share many similarities including their basic gene arrangement, modes of transmission, intracellular replication pathways and clinical consequences: both result in AIDS. However, HIV‐2 is characterised by lower transmissibility and reduced likelihood of progression to AIDS. The underlying mechanistic differences between these two infections illuminate broader issues of retroviral pathogenesis, which remain incompletely understood. Comparisons between these two infections from epidemiological, clinical, virologic and immunologic viewpoints provide a basis for hypothesis generation and testing in this 'natural experiment' in viral pathogenesis. In terms of epidemiology, HIV‐2 remains largely confined to West Africa, whereas HIV‐1 extends worldwide. Clinically, HIV‐2 infected individuals seem to dichotomise, most remaining long‐term non‐progressors, whereas most HIV‐1 infected individuals progress. When clinical progression occurs, both diseases demonstrate very similar pathological processes, although progression in HIV‐2 occurs at higher CD4 counts. Plasma viral loads are consistently lower in HIV‐2, as are average levels of immune activation. Significant differences exist between the two infections in all components of the immune system. For example, cellular responses to HIV‐2 tend to be more polyfunctional and produce more IL‐2; humoral responses appear broader with lower magnitude intratype neutralisation responses; innate responses appear more robust, possibly through differential effects of tripartite motif protein isoform 5 alpha. Overall, the immune response to HIV‐2 appears more protective against disease progression suggesting that pivotal immune factors limit viral pathology. If such immune responses could be replicated or induced in HIV‐1 infected patients, they might extend survival and reduce requirements for antiretroviral therapy. Copyright © 2013 John Wiley & Sons, Ltd.